Interactive effects of bismuth exposure (water and diet) and temperature on snail fatty acid composition, antioxidant enzymes and lipid peroxidation - Fadhlaoui, Mariem; Pearce, Nolan J. T.; Lavoie, Isabelle; Fortin, Claude (Frontiers in Environmental Chemistry, 2024)
Despite the growing prevalence of Bismuth (Bi), very little research has been carried to assess its potential toxic effects on aquatic organisms. This study aimed to address this gap by investigating the interactive effects of Bi exposure and elevated temperature on freshwater snails of the genus Lymnaea, specifically on their fatty acid (FA) profiles, oxidative stress markers (superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione S-transferase (GST)) and lipid peroxidation (malondialdehyde (MDA) content). Bismuth exposure was introduced through two distinct routes: (i) food via Bi-exposed biofilm (grown under 2 μM Bi), and (ii) water (2 μM Bi). Exposed snails were maintained at two temperatures, 19°C and 25°C, over a duration of 14 days. Bi bioaccumulation occurred in Bi-exposed biofilm concurrently with a pronounced increase in polyunsaturated fatty acids (PUFA), likely as a protective mechanism to preserve cell structure and integrity. Bi bioaccumulation also occurred in snails with their FA composition largely reflecting the composition of their dietary source highlighting the direct link between diet and snail FA profiles. Additionally, the antioxidant enzymes studied exhibited diverse responses under Bi exposure and thermal stress, suggesting the induction of oxidative stress in snails. SOD activity increased at 25°C, suggesting a thermal stress. CAT activity remained high under all conditions, unaffected by temperature or Bi exposure. GPx levels increased in snails fed with Bi-laden biofilm, particularly at 19°C. GST activity showed great variability with a significant three-way interaction. The observed elevation in MDA levels among Bi-exposed snails suggested a potential deficiency in their antioxidant enzyme systems, leading to an increased susceptibility to lipid peroxidation. This research highlights the complex interaction between Bi contamination, temperature, and the physiological responses of aquatic organisms, and reveals the need for future research into the environmental impact of Bi 4 in aquatic ecosystems. We further highlight the importance of food for Bi transfer to higher consumers and considering dietborne exposures in ecotoxicological studies.